Strong, antioxidant, and biodegradable gelatin methacryloyl composite hydrogel for oxidative stress protection in Schwann cells - Han, Hongyang; Ji, Dongcao; Yang, Shu; Pang, Bo; Chen, Xi; Zhu, Jiaqi; Cao, Wenxin; Song, Tao (Frontiers in Bioengineering and Biotechnology, 2025)
Gelatin methacryloyl (GelMA), a biomaterial widely used in tissue engineering, exhibits excellent biocompatibility and cell adhesion properties. However, its poor mechanical strength and functional monotony restrict broader clinical applications of this material. In this study, we introduced sodium acrylate (SA) and tannic acid (TA) into the GelMA system via a two-step crosslinking strategy, successfully fabricating a GelMA/SA–TA (GST) composite hydrogel that achieved dual enhancement of mechanical and antioxidant properties. The incorporation of SA and TA significantly improved the mechanical performance of the hydrogel, which exhibited a maximum tensile modulus of 31.83 ± 2.84 kPa. At the same time, TA endowed the hydrogel with exceptional antioxidant ability, resulting in a free radical scavenging rate of 89.93% ± 0.9% in vitro. Biological tests revealed that the GST hydrogel effectively alleviated oxidative stress damage in rat Schwann cells (RSC96) by suppressing the generation of reactive oxygen species (ROS) and promoting the secretion of brain-derived neurotrophic factor (BDNF). This work presents the first report of an antioxidant hydrogel capable of protecting Schwann cells without compromising their mechanical integrity, highlighting its transformative potential for peripheral nerve injury repair. The synergistic SA–TA modification strategy provides new insights into the design of multifunctional biomaterials for neural regeneration applications.